Hubungan Asupan Gizi dari Makanan Cepat Saji, Aktivitas Fisik dan Tingkat Stres dengan Kejadian Gizi Lebih pada Remaja - Hasnah, Nurul Hayatul (Pontianak Nutrition Journal (PNJ), 2024)
Overnutrition status is an accumulation of excess fat that accumulates in the body, causing various health problems such as non-communicable diseases. Adolescents who experience excess nutrition have a 70% risk of experiencing overweight or obesity as adults. This study aims to determine the relationship between intake of nutrients from fast food, physical activity and stress levels with the incidence of overweight in adolescents at SMK Muhammadiyah 9 Jakarta in 2022. This study used an observational analytic study design and a cross sectional approach. This research was conducted on 96 adolescents in class X and XI at SMK Muhammadiyah 9 Jakarta. Data on fast food nutrient intake was obtained by filling out the SQ-FFQ form through interviews, physical activity data was obtained by filling out the PAQ-A questionnaire independently, and stress level data was obtained by filling out the DASS-14 questionnaire independently, and data on excess nutrition was obtained through Anthropometric measurements are then interpreted into a BMI/U z – score. Total respondents in this study were 96 people. The proportion of adolescents who experienced excess nutrition was 68.8%. Based on the results of data analysis, the results showed that there was a significant relationship between the type of fast food (p value = 0.000), the frequency of fast food (p value = 0.000), the amount of fast food nutrients, energy and fat (p value = 0.000), physical activity (p value = 0.000) and stress levels (p value = 0.000) with the incidence of overweight in adolescents at SMK Muhammadiyah 9 Jakarta.Keywords: Nutrient Intake, Fast Food, Physical Activity, Stress Level, Over nutrition